Chromium effects on the microstructural, mechanical and thermal properties of a rapidly solidified eutectic Sn-Ag alloy - Abbas, Sanaa Razzaq; Gumaan, Mohammed S.; Shalaby, Rizk Mostafa (Emerald Publishing Limited, 2019)
Purpose This study aims to investigate the chromium (Cr) effects on the microstructural, mechanical and thermal properties of melt-spun Sn-3.5Ag alloy. Design/methodology/approach Ternary melt-spun Sn-Ag-Cr alloys were investigated using X-ray diffractions, scanning electron microscope, dynamic resonance technique, instron machine, Vickers hardness tester and differential scanning calorimetry. Findings The results revealed that the Ag3Sn intermetallic compound (IMC) and ?-Sn have been refined because of the hard inclusions (Cr atoms) effects, causing lattice distortion increasing these alloys. The tensile results of Sn96.4-Ag3.5-Cr0.1 alloy showed an improvement in Youngs modulus more than 100 per cent (42.16?GPa), ultimate tensile strength (UTS) by 9.4 per cent (23.9?MPa), compared with the eutectic Sn-Ag alloy due to the high concentration of Ag3Sn and their uniform distribution. Shortage in the internal friction (Q?1) of about 54 per cent (45.1) and increase in Vickers hardness of about 7.4 per cent (142.1?MPa) were also noted. Hexagonal Ag3Sn formation led to low toughness values compared to the eutectic Sn-Ag alloy, which may have resulted from the mismatching among hexagonal Ag3Sn phase with orthorhombic Ag3Sn and ?-Sn phases. Mechanically, the values of Youngs modulus have been increased, with increasing chromium content, whereas the UTS and toughness values have been decreased. The opposite of this trend appeared in Sn95.8-Ag3.5-Cr0.7 alloy, which may have been due to high lattice distortion (? = 16.5??10?4) compared to the other alloys. Increase in the melting temperature Tm, ?H, Cp and ?T was because of Ag3Sn IMC formation. The low toughness of Sn96-Ag3.5-Cr0.5 and Sn95.8-Ag3.5-Cr0.7 (109.56?J/m3 and 35.66?J/m3), relatively high melting temperature Tm (223.22C and 222.65C) and low thermal conductivity and thermal diffusivity (32.651 w.m?1.k?1 and 0.314 m2/s) make them undesirable in the soldering process. The high UTS, high E, high thermal conductivity and diffusivity, low creep rate and low electrical resistivity, which have occurred with 0.1?Wt.% of Cr, make this alloy desirable and reliable for soldering applications and electronic assembly. Originality/value This study provides chromium effects on the structure of the eutectic Sn-Ag rapidly solidified by melt-spinning technique. In this paper, the authors compared the elastic modulus of the melt-spun compositions, which have been resulted from the Static method with that have been resulted from the Dynamic method. This paper presents new improvements in mechanical and thermal performance.